Graphene heating film for warmer and preparation method thereof
By bonding the composite film to the graphene heating film, the dust accumulation and static electricity problems in the heater are solved, the stable thermal conductivity and safety of the heating film are ensured, and the service life of the equipment is extended.
Patent Information
- Application Number
- CN202411851474.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
In existing heaters, dust is easily accumulated between the graphene heating film and the shell, resulting in poor heat dissipation, serious static electricity, and even short circuits, resulting in too high temperature and causing scalds.
A composite film is bonded to the surface of the graphene heating film, which consists of PTFE fiber film, starch-coated epoxy resin and epoxy resin adhesive. A stable composite film is formed through cross-linking reaction to ensure the thermal conductivity and insulation properties of the heating film.
Effectively prevent dust accumulation and static conduction, maintain the stable thermal conductivity of the heating film, avoid excessive temperature, extend the service life of the heater, and improve the safety of use.
Smart Images

Figure CN119663636A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heating materials, and in particular to a graphene heating film for a heater and a preparation method thereof. Background Art
[0002] Since graphene was first prepared in 2004, its excellent physical properties have attracted extensive attention from many scholars. Graphene has excellent electrical conductivity, and its two-dimensional planar structure makes it easier to form a conductive network in the matrix than zero-dimensional or one-dimensional conductive materials. Therefore, graphene has shown good application prospects in the field of electric heating, with moderate resistivity and excellent processing and molding characteristics.
[0003] When graphene film is used in electric heating elements such as electric heaters, its heating temperature can rise rapidly, thereby quickly achieving the heating effect people need. However, the temperature of a single layer of graphene rises very quickly, and the maximum temperature can reach 200-300℃. If you are not careful, burns may occur. The operating temperature of the heater shell is generally 40-60℃, which can feel warm when touched but not hot. Therefore, when people design graphene layers for heaters, they often separate the heating graphene layer from the touchable shell of the heater surface to ensure that there is a certain distance between the heating graphene layer and the heater shell. The air acts as a medium for transferring temperature, so that the high temperature of the heating graphene with an operating temperature of 200-300℃ can be reduced to a temperature suitable for human touch when it is transferred to the heater shell. In addition, by isolating the contact between the graphene layer and the heater shell, it can also prevent the graphene from short-circuiting during electric heating and causing the shell to be charged, effectively preventing people from getting electric shock when using the heater.
[0004] However, during people's long-term daily use, dust is easily accumulated between the outer shell of the heater and the graphene heating layer. The accumulation of dust is not conducive to heat dissipation, and the dust will transfer static electricity, thereby making the outer shell of the heater charged. Static electricity is more likely to occur when used in a dry environment in winter, further aggravating the accumulation of dust. As a result, after long-term use, a lot of dust will adhere to the outside of the graphene heating film, and even a short circuit will occur, causing the temperature of the graphene heating film to become higher. If the temperature is too high, burns are likely to occur. Therefore, the present application provides a graphene heating film for a heater and a preparation method thereof. A layer of composite film for transferring temperature and insulation is bonded to the surface of the graphene layer. The presence of the film can prevent the temperature of the graphene heating film from rising sharply even if it is used for a long time, and it has a good heating and heating function. Summary of the invention
[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a graphene heating film for a heater and a preparation method thereof.
[0006] A method for preparing a graphene heating film for a heater comprises the following steps:
[0007] S1: Preparation of composite PTFE fiber membrane
[0008] The PTFE emulsion is added to the potato starch solution, stirred and allowed to stand to obtain a spinning solution A, starch powder and DMSO are mixed, cellulose acetate is added, heated and stirred to obtain a spinning solution B, the spinning solution A and the spinning solution B are mixed in equal volumes, placed in a spinneret for centrifugal spinning, and a composite PTFE fiber membrane is obtained;
[0009] S2: Preparation of starch-coated epoxy resin and epoxy resin adhesive
[0010] Dissolving water-soluble starch in deionized water to obtain a liquid medium, and then adding epoxy resin to the liquid medium to prepare starch-coated epoxy resin; adding graphene powder to deionized water to obtain a graphene dispersion, mixing concentrated sulfuric acid and concentrated nitric acid to prepare a mixed acid, mixing the mixed acid with the graphene dispersion to prepare treated graphene, adding the treated graphene to an emulsifier PEG for ultrasonic dispersion to obtain a treated liquid, and then adding the treated liquid to the epoxy resin for mixing to obtain an epoxy resin adhesive;
[0011] S3: Preparation of cross-linked composite membrane
[0012] The starch-coated epoxy resin and the composite PTFE fiber membrane are cross-linked, cleaned and dried to obtain a cross-linked composite membrane;
[0013] S4: Preparation of graphene heating film for heaters
[0014] Graphene is mixed with deionized water to form a graphene suspension, and then the cross-linked composite film and the graphene dispersion are hot-pressed to obtain a conductive heating film. Wires are connected to the conductive heating film, and then epoxy resin adhesive is coated and the cross-linked composite film is attached, and hot-pressed to obtain a graphene heating film for heaters.
[0015] Furthermore, step S1 of preparing the composite PTFE fiber membrane comprises the following steps:
[0016] S1.1: At room temperature of 22-26°C, potato starch is added to a 2-2.5wt% NaOH aqueous solution and stirred continuously for 3-4h to form a potato starch solution, wherein the material-liquid ratio of potato starch to NaOH is 3:(10-11)g / L, and then an equal volume of PTFE emulsion is added to the potato starch solution and stirred for 2-3h, and then allowed to stand for 3-4h to obtain a spinning solution A;
[0017] S1.2: Mix starch powder and DMSO and heat in a water bath to 70-80°C, the starch powder and DMSO solid-liquid ratio is 1:(9-10) g / L, stir magnetically for 20-24 hours to obtain spinning solution, add 10-12% of the total mass of cellulose acetate to the spinning solution, heat and stir again for 30-40 minutes, let stand to degas, and obtain spinning solution B for standby use;
[0018] S1.3: Mix spinning solution A and spinning solution B in equal volumes, place in a spinneret, centrifuge at a speed of 900-1000 rpm, collect at a distance of 95-100 mm, and perform centrifugal spinning at a humidity of 45-50% and a temperature of 40-60° C. to obtain a composite PTFE fiber membrane.
[0019] Furthermore, the spinneret needle in step S1.3 has a specification of 25G dispensing needle.
[0020] Furthermore, step S2 prepares starch-coated epoxy resin and epoxy resin adhesive, comprising the following steps:
[0021] S2.1: dissolving water-soluble starch in deionized water at a solid-liquid ratio of 1:(7-8) g / L to obtain a liquid medium, then adding 20-25% of the system mass of epoxy resin to the liquid medium, stirring evenly to prepare a rheological phase, and keeping stirring to react the rheological phase at room temperature of 22-26°C for 2-3 hours. After the reaction is completed, washing with anhydrous ethanol three times, and then drying in a vacuum oven to obtain starch-coated epoxy resin;
[0022] S2.2: Add graphene powder to deionized water at a solid-liquid ratio of 1:(4-5) g / L to obtain a graphene dispersion, mix concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:(6-7) to prepare a mixed acid, wait for the mixed acid to cool to room temperature 22-26°C, add the mixed acid to a reaction vessel and mix it with the graphene dispersion, the volume ratio of the mixed acid to the graphene dispersion is 3:(4-5), put it in a constant temperature water bath at 60-80°C, start the reaction and stir for 2-3h, wash the product repeatedly with distilled water and anhydrous ethanol, filter it until it is neutral, and then place it in a vacuum oven at 55-65°C to dry for 18-20h to obtain treated graphene;
[0023] S2.3: Add the treated graphene to the emulsifier PEG and ultrasonically disperse for 20-25 minutes. The solid-liquid ratio of the treated graphene and the emulsifier PEG is 1: (3-4) g / L to obtain a treated liquid. Then, add the treated liquid to the epoxy resin and mix them together in a mixer for 30-40 minutes to obtain an epoxy resin adhesive.
[0024] Furthermore, step S3 of preparing a cross-linked composite membrane comprises the following steps:
[0025] S3.1: placing the prepared starch-coated epoxy resin and composite PTFE fiber membrane in a sealed container containing a 25-30% by mass glutaraldehyde aqueous solution, and steam crosslinking at room temperature of 22-26°C for 24-26 hours;
[0026] S3.2: Then take out the cross-linked fiber membrane, soak it in a 0.1-0.2M glycine aqueous solution for 3-5 hours, and then wash it repeatedly with PBS for 2-3 times to remove the glutaraldehyde solution. Finally, place it in a 40-45℃ oven for ventilation and drying for 4-5 hours to obtain a cross-linked composite membrane.
[0027] Furthermore, step S4 prepares a graphene heating film for a heater, comprising the following steps:
[0028] S4.1: firstly, anhydrous ethanol and graphene are mixed in a solid-liquid ratio of 2:(11-13) g / L, and a graphene dispersion is obtained after ultrasonic treatment, and then deionized water is added to prepare a graphene suspension having a graphene content of 0.5-1 wt%;
[0029] S4.2: coating the graphene suspension on the surface of the cross-linked composite film, and then placing it on a hot press at a temperature of 55-60° C. and a pressure of 1-1.5 MPa for hot pressing and drying, and after drying, obtaining a conductive heating film;
[0030] S4.3: Connect two copper foil wires to the graphene-covered side of the conductive heating film, apply a layer of epoxy resin adhesive, and stick a cross-linked composite film on it. Press it on a hot press with a pressure of 1-1.5MPa for 10-30s to obtain a graphene heating film for heaters.
[0031] A graphene heating film for a heater is prepared by the above-mentioned method for preparing a graphene heating film for a heater.
[0032] Compared with the prior art, the present invention has at least the following beneficial effects:
[0033] 1. The present invention mixes starch, DMSO and cellulose acetate to prepare a spinning solution B and uses the spinning solution B to prepare a composite PTFE fiber membrane. The fiber membrane prepared by cellulose has good mechanical strength and toughness, good tensile strength and durability. The introduction of starch by DMSO can make the starch and cellulose evenly mixed, thereby improving the stability of the fiber membrane. Moreover, through the reasonable proportion and process conditions of starch, cellulose acetate and DMSO, the thermal conductivity of the composite membrane will not change after working for a long time, thereby ensuring the working performance of the heater when the prepared graphene heating film is used in the heater and extending the service life of the heater.
[0034] 2. The present invention blends and spins a spinning solution A prepared by mixing potato starch and PTFE emulsion as the main body and a spinning solution B prepared by mixing starch and cellulose acetate to obtain a composite PTFE fiber membrane. Potato starch and PTFE emulsion, starch can be evenly mixed and compatible with cellulose. Through the mutual compatibility of starch, cellulose and PTFE are cross-linked to a certain extent, thereby improving the thermal stability of the membrane. In addition, the large-scale gaps in the structure of the cross-linked PTFE and cellulose are filled by small starch molecules. The membrane produced by spinning has good barrier properties and electrical resistance, can prevent leakage, and has stable thermal conductivity to ensure the safe use of the heater.
[0035] 3. The present invention prepares starch-coated epoxy resin and cross-links it with a composite PTFE fiber membrane to obtain a cross-linked composite. The starch-coated epoxy resin has strong adhesion properties. After cross-linking with PTFE, the surface starch is polymerized to make the epoxy resin and the surface of the composite PTFE fiber membrane well combined, and the subsequent graphene is tightly bonded by the viscosity of the epoxy resin to form a conductive heating film that is not easy to fall off and decompose. The epoxy resin adhesive is then used to bond the wire and another cross-linked composite film. While the graphene is conductive and heats up, leakage is prevented, and dust accumulated after the heater is used for a long time is prevented from invading the junction of the graphene layer and the copper foil wire, thereby ensuring the safety of the heater. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0037] Figure 1 This is a flow chart of a method for preparing a graphene heating film for a heater adopted in an embodiment of the present invention. DETAILED DESCRIPTION
[0038] The following is a detailed description of a graphene heating film for a heater and a preparation method thereof provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0039] Embodiment 1:
[0040] A method for preparing a graphene heating film for a heater, such as Figure 1 As shown, the following steps are included:
[0041] S1: Preparation of composite PTFE fiber membrane
[0042] S1.1: At room temperature of 22°C, potato starch was added to a 2wt% NaOH aqueous solution and stirred continuously for 3 hours to form a potato starch solution, wherein the material-liquid ratio of potato starch to NaOH was 3:10 g / L, and then an equal volume of PTFE emulsion was added to the potato starch solution and stirred for 2 hours, and then allowed to stand for 3 hours to obtain a spinning solution A;
[0043] S1.2: Mix starch powder and DMSO and heat them in a water bath to 70°C, with the starch powder and DMSO solid-liquid ratio being 1:10 g / L. Stir them magnetically for 24 h to obtain a spinning solution. Add 10% of the total mass of cellulose acetate to the spinning solution, heat and stir again for 30 min, and let stand to degas to obtain a spinning solution B for later use.
[0044] S1.3: Mix spinning solution A and spinning solution B in equal volumes, place in a spinneret, use a 25G dispensing needle, a centrifugal speed of 900 rpm, a collection distance of 95 mm, and perform centrifugal spinning in an environment of 45% humidity and 40°C to obtain a composite PTFE fiber membrane.
[0045] S2: Preparation of starch-coated epoxy resin and epoxy resin adhesive
[0046] S2.1: Dissolve water-soluble starch in deionized water at a solid-liquid ratio of 1:8 g / L to obtain a liquid medium, then add 20% of the system mass of epoxy resin to the liquid medium, stir evenly to form a rheological phase, keep stirring and react the rheological phase at room temperature of 22°C for 2 hours. After the reaction is completed, wash it three times with anhydrous ethanol, and then dry it in a vacuum oven to obtain starch-coated epoxy resin;
[0047] S2.2: Add graphene powder to deionized water at a solid-liquid ratio of 1:4 g / L to obtain a graphene dispersion, mix concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:7 to prepare a mixed acid, wait for the mixed acid to cool to room temperature 22°C, add the mixed acid to a reaction vessel and mix it with the graphene dispersion, the volume ratio of the mixed acid to the graphene dispersion is 3:4, put it in a 60°C constant temperature water bath, start the reaction and stir for 2 hours, wash the product repeatedly with distilled water and anhydrous ethanol, filter it until it is neutral, and then place it in a 55°C vacuum oven to dry for 18 hours to obtain treated graphene;
[0048] S2.3: Add the treated graphene to the emulsifier PEG and ultrasonically disperse it for 20 minutes. The solid-liquid ratio of the treated graphene and the emulsifier PEG is 1:3 g / L to obtain a treated liquid. Then add the treated liquid to the epoxy resin and mix them together in a mixer for 30 minutes to obtain an epoxy resin adhesive.
[0049] S3: Preparation of cross-linked composite membrane
[0050] S3.1: Place the prepared starch-coated epoxy resin and composite PTFE fiber membrane in a sealed container containing a 25% by mass glutaraldehyde aqueous solution and steam crosslink for 24 hours at room temperature of 22°C;
[0051] S3.2: The cross-linked fiber membrane was then taken out and immersed in a 0.1 M glycine aqueous solution for 3 h, and then repeatedly washed with PBS for 3 times to remove the glutaraldehyde solution. Finally, it was placed in a 40°C oven for ventilation and drying for 4 h to obtain a cross-linked composite membrane.
[0052] S4: Preparation of graphene heating film for heaters
[0053] S4.1: firstly, anhydrous ethanol and graphene are mixed in a solid-liquid ratio of 2:13 g / L, and a graphene dispersion is obtained after ultrasonic treatment, and then deionized water is added to prepare a graphene suspension having a graphene content of 0.5 wt%;
[0054] S4.2: coating the graphene suspension on the surface of the cross-linked composite film, and then placing it on a hot press at a temperature of 55° C. and a pressure of 1 MPa for hot pressing and drying, and after drying, obtaining a conductive heating film;
[0055] S4.3: Connect two copper foil wires to the graphene-covered side of the conductive heating film, apply a layer of epoxy resin adhesive, and stick a cross-linked composite film on it. Press it on a hot press with a pressure of 1 MPa for 30 seconds to obtain a graphene heating film for heaters.
[0056] Embodiment 2:
[0057] A method for preparing a graphene heating film for a heater, such as Figure 1 As shown, the following steps are included:
[0058] S1: Preparation of composite PTFE fiber membrane
[0059] S1.1: At room temperature of 26°C, potato starch was added to a 2wt% NaOH aqueous solution and stirred continuously for 4 hours to form a potato starch solution, wherein the material-liquid ratio of potato starch to NaOH was 3:10 g / L, and then an equal volume of PTFE emulsion was added to the potato starch solution and stirred for 3 hours, and then allowed to stand for 4 hours to obtain a spinning solution A;
[0060] S1.2: Mix starch powder and DMSO and heat them in a water bath to 80°C, with the starch powder and DMSO solid-liquid ratio being 1:10 g / L. Stir them magnetically for 20 h to obtain a spinning solution. Add 10% of the total mass of cellulose acetate to the spinning solution, heat and stir again for 40 min, and let stand to degas to obtain a spinning solution B for later use.
[0061] S1.3: Mix spinning solution A and spinning solution B in equal volumes, place in a spinneret, select a dispensing needle with a needle specification of 25G, set the centrifugal speed to 1000rpm, set the collection distance to 100mm, and perform centrifugal spinning in an environment of 50% humidity and 60°C to obtain a composite PTFE fiber membrane.
[0062] S2: Preparation of starch-coated epoxy resin and epoxy resin adhesive
[0063] S2.1: Dissolve water-soluble starch in deionized water at a solid-liquid ratio of 1:8 g / L to obtain a liquid medium, then add 20% of the system mass of epoxy resin to the liquid medium, stir evenly to form a rheological phase, keep stirring and react the rheological phase at room temperature 26°C for 3 hours. After the reaction is completed, wash it three times with anhydrous ethanol, and then dry it in a vacuum oven to obtain starch-coated epoxy resin;
[0064] S2.2: Add graphene powder to deionized water at a solid-liquid ratio of 1:4 g / L to obtain a graphene dispersion, mix concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:7 to prepare a mixed acid, wait for the mixed acid to cool to room temperature 26°C, add the mixed acid to a reaction vessel and mix it with the graphene dispersion, the volume ratio of the mixed acid to the graphene dispersion is 3:4, put it in a constant temperature water bath at 80°C, start the reaction and stir for 3 hours, wash the product repeatedly with distilled water and anhydrous ethanol, filter it until it is neutral, and then place it in a vacuum oven at 65°C to dry for 20 hours to obtain treated graphene;
[0065] S2.3: Add the treated graphene to the emulsifier PEG and ultrasonically disperse it for 25 minutes. The solid-liquid ratio of the treated graphene and the emulsifier PEG is 1:4 g / L to obtain a treated liquid. Then, add the treated liquid to the epoxy resin and mix them together in a mixer for 40 minutes to obtain an epoxy resin adhesive.
[0066] S3: Preparation of cross-linked composite membrane
[0067] S3.1: Place the prepared starch-coated epoxy resin and composite PTFE fiber membrane in a sealed container containing a 25% by mass glutaraldehyde aqueous solution and steam crosslink for 26 hours at room temperature of 26°C;
[0068] S3.2: The cross-linked fiber membrane was then taken out and immersed in a 0.15 M glycine aqueous solution for 3 h, and then repeatedly washed with PBS for 3 times to remove the glutaraldehyde solution. Finally, it was placed in a 45°C oven for ventilation and drying for 5 h to obtain a cross-linked composite membrane.
[0069] S4: Preparation of graphene heating film for heaters
[0070] S4.1: firstly, anhydrous ethanol and graphene are mixed in a solid-liquid ratio of 2:13 g / L, and a graphene dispersion is obtained after ultrasonic treatment, and then deionized water is added to prepare a graphene suspension having a graphene content of 0.5 wt%;
[0071] S4.2: coating the graphene suspension on the surface of the cross-linked composite film, and then placing it on a hot press at a temperature of 60° C. and a pressure of 1 MPa for hot pressing and drying, and after drying, obtaining a conductive heating film;
[0072] S4.3: Connect two copper foil wires to the graphene-covered side of the conductive heating film, apply a layer of epoxy resin adhesive, and stick a cross-linked composite film on it. Press it on a hot press with a pressure of 1 MPa for 10 seconds to obtain a graphene heating film for heaters.
[0073] Embodiment 3:
[0074] A method for preparing a graphene heating film for a heater, such as Figure 1 As shown, the following steps are included:
[0075] S1: Preparation of composite PTFE fiber membrane
[0076] S1.1: At room temperature of 22°C, potato starch was added to a 2.5wt% NaOH aqueous solution and stirred continuously for 3 hours to form a potato starch solution, wherein the material-liquid ratio of potato starch to NaOH was 3:11 g / L, and then an equal volume of PTFE emulsion was added to the potato starch solution and stirred for 2 hours, and then allowed to stand for 4 hours to obtain a spinning solution A;
[0077] S1.2: Mix starch powder and DMSO and heat them in a water bath to 70°C, with the starch powder and DMSO solid-liquid ratio being 1:9 g / L. Stir them magnetically for 24 h to obtain a spinning solution. Add 10% of the total mass of cellulose acetate to the spinning solution, heat and stir again for 30 min, and let stand to degas to obtain a spinning solution B for later use.
[0078] S1.3: Mix spinning solution A and spinning solution B in equal volumes, place in a spinneret, select a dispensing needle with a needle specification of 25G, set the centrifugal speed to 900rpm, set the collection distance to 95mm, and perform centrifugal spinning in an environment with a humidity of 45% and a temperature of 60°C to obtain a composite PTFE fiber membrane.
[0079] S2: Preparation of starch-coated epoxy resin and epoxy resin adhesive
[0080] S2.1: Dissolve water-soluble starch in deionized water at a solid-liquid ratio of 1:7 g / L to obtain a liquid medium, then add 25% of the system mass of epoxy resin to the liquid medium, stir evenly to form a rheological phase, keep stirring and react the rheological phase at room temperature 22°C for 2 hours. After the reaction is completed, wash it three times with anhydrous ethanol, and then dry it in a vacuum oven to obtain starch-coated epoxy resin;
[0081] S2.2: Add graphene powder to deionized water at a solid-liquid ratio of 1:5 g / L to obtain a graphene dispersion, mix concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:6 to prepare a mixed acid, wait for the mixed acid to cool to room temperature 22°C, add the mixed acid to a reaction vessel and mix it with the graphene dispersion, the volume ratio of the mixed acid to the graphene dispersion is 3:5, put it in a 60°C constant temperature water bath, start the reaction and stir for 2 hours, wash the product repeatedly with distilled water and anhydrous ethanol, filter it until it is neutral, and then place it in a 55°C vacuum oven to dry for 18 hours to obtain treated graphene;
[0082] S2.3: Add the treated graphene to the emulsifier PEG and ultrasonically disperse it for 20 minutes. The solid-liquid ratio of the treated graphene and the emulsifier PEG is 1:4 g / L to obtain a treated liquid. Then add the treated liquid to the epoxy resin and mix them together in a mixer for 40 minutes to obtain an epoxy resin adhesive.
[0083] S3: Preparation of cross-linked composite membrane
[0084] S3.1: Place the prepared starch-coated epoxy resin and composite PTFE fiber membrane in a sealed container containing a 25% by mass glutaraldehyde aqueous solution and steam crosslink for 24 hours at room temperature of 22°C;
[0085] S3.2: The cross-linked fiber membrane was then taken out and immersed in a 0.1 M glycine aqueous solution for 3 h, and then repeatedly washed with PBS for 3 times to remove the glutaraldehyde solution. Finally, it was placed in a 40°C oven for ventilation and drying for 4 h to obtain a cross-linked composite membrane.
[0086] S4: Preparation of graphene heating film for heaters
[0087] S4.1: firstly, anhydrous ethanol and graphene are mixed in a solid-liquid ratio of 2:11 g / L, and a graphene dispersion is obtained after ultrasonic treatment, and then deionized water is added to prepare a graphene suspension having a graphene content of 1 wt%;
[0088] S4.2: coating the graphene suspension on the surface of the cross-linked composite film, and then placing it on a hot press at a temperature of 55° C. and a pressure of 1 MPa for hot pressing and drying, and after drying, obtaining a conductive heating film;
[0089] S4.3: Connect two copper foil wires to the graphene-covered side of the conductive heating film, apply a layer of epoxy resin adhesive, and stick a cross-linked composite film on it. Press it on a hot press with a pressure of 1 MPa for 10 seconds to obtain a graphene heating film for heaters.
[0090] Comparative Example 1:
[0091] Compared with Example 1, the difference of Comparative Example 1 is that DMSO is not added in step S1.2, but water is used instead of DMSO, and cellulose acetate is mixed with starch powder to prepare spinning solution B, specifically "S1.1: at room temperature 22°C, potato starch is added to a 2.0wt% NaOH aqueous solution and stirred continuously for 3h to form a potato starch solution, the material-liquid ratio of potato starch to NaOH is 3:10g / L, then an equal volume of PTFE emulsion is added to the potato starch solution, stirring is continued for 2h, and standing is performed for 4h to obtain spinning solution A;
[0092] S1.2: Mix starch powder and water, heat in a water bath to 70°C, the starch powder and water ratio is 1:10 g / L, stir magnetically for 24 h to obtain spinning solution, add 10% of the total mass of cellulose acetate to the spinning solution, heat and stir again for 30 min, let stand to degas, obtain spinning solution B, and set aside;
[0093] S1.3: Mix spinning solution A and spinning solution B in equal volumes, place them in a spinneret, select a dispensing needle with a needle specification of 25G, set the centrifugal speed to 900rpm, and the collection distance to 95mm. Centrifugal spinning is performed in an environment with a humidity of 45% and a temperature of 40°C to obtain a composite PTFE fiber membrane. The prepared graphene heating film for heater is recorded as Comparative Example 1.
[0094] Comparative Example 2:
[0095] Compared with Example 1, the difference of Comparative Example 2 is that cellulose acetate is not added in step S1.2, but a spinning solution prepared by mixing starch powder and DMSO is directly used to prepare spinning solution B, specifically: "S1.1: At room temperature 22°C, potato starch is added to a 2.0wt% NaOH aqueous solution and stirred continuously for 3h to form a potato starch solution, the material-liquid ratio of potato starch to NaOH is 3:10g / L, and then an equal volume of PTFE emulsion is added to the potato starch solution and stirred for 2h, and then allowed to stand for 4h to obtain spinning solution A;
[0096] S1.2: Starch powder and DMSO were mixed at a material-liquid ratio of 1:10 g / L, heated in a water bath to 70°C, and magnetically stirred for 24 h to obtain a spinning solution. The spinning solution was allowed to stand for degassing to obtain a spinning solution B for later use;
[0097] S1.3: Mix spinning solution A and spinning solution B in equal volumes, place in a spinneret, select a dispensing needle with a needle specification of 25G, set the centrifugal speed to 900rpm, set the collection distance to 95mm, and perform centrifugal spinning in an environment with a humidity of 45% and a temperature of 40°C to obtain a composite PTFE fiber membrane. The prepared graphene heating film for heater is recorded as Comparative Example 2.
[0098] Comparative Example 3:
[0099] Compared with Example 1, the difference of Comparative Example 3 is that potato starch is not added in step S1.1, and PTFE emulsion is directly used as spinning solution A, specifically: "S1.1: adding an equal volume of PTFE emulsion to a 2.0wt% NaOH aqueous solution at room temperature of 22°C, stirring for 2h, and standing for 3h to obtain spinning solution A;
[0100] S1.2: Mix starch powder and DMSO and heat them in a water bath to 70°C, with the starch powder and DMSO solid-liquid ratio being 1:10 g / L. Stir them magnetically for 24 h to obtain a spinning solution. Add 10% of the total mass of cellulose acetate to the spinning solution, heat and stir again for 30 min, and let stand to degas to obtain a spinning solution B for later use.
[0101] S1.3: Mix spinning solution A and spinning solution B in equal volumes, place in a spinneret, select a dispensing needle with a needle specification of 25G, set the centrifugal speed to 900rpm, set the collection distance to 95mm, and perform centrifugal spinning in an environment with a humidity of 45% and a temperature of 40°C to obtain a composite PTFE fiber membrane. The prepared graphene heating film for heater is recorded as Comparative Example 3.
[0102] Comparative Example 4:
[0103] Compared with Example 1, the difference of Comparative Example 4 is that potato starch is not added in step S1.1, and starch powder is not added in step S1.2, specifically: “S1.1: adding an equal volume of PTFE emulsion to a 2.0 wt% NaOH aqueous solution at room temperature of 22° C., stirring for 2 h, and standing for 3 h to obtain spinning solution A;
[0104] S1.2: Mix cellulose acetate and DMSO in a volume ratio of 1:10, heat in a water bath to 70°C, stir magnetically for 24 hours, and let stand to degas to obtain spinning solution B for later use;
[0105] S1.3: Mix spinning solution A and spinning solution B in equal volumes, place in a spinneret, select a dispensing needle with a needle specification of 25G, set the centrifugal speed to 900rpm, set the collection distance to 95mm, and perform centrifugal spinning in an environment of 45% humidity and 40°C to obtain a composite PTFE fiber membrane. The prepared graphene heating film for heater is recorded as Comparative Example 4.
[0106] Comparative Example 5:
[0107] Compared with Example 1, the difference of Comparative Example 5 is that step S1.1 is not performed, and the spinning solution B prepared in step S1.2 is directly spun, specifically:
[0108] S1.1: Mix starch powder and DMSO and heat them in a water bath to 70°C, with the starch powder and DMSO solid-liquid ratio being 1:10 g / L. Stir them magnetically for 24 h to obtain a spinning solution. Add 10% of the total mass of cellulose acetate to the spinning solution, heat and stir again for 30 min, and let stand to degas to obtain a spinning solution B for later use.
[0109] S1.2: Place the spinning solution B in a spinneret, select a dispensing needle with a needle specification of 25G, set the centrifugal speed to 900rpm, set the collection distance to 95mm, and perform centrifugal spinning in an environment with a humidity of 45% and a temperature of 40°C to obtain a composite PTFE fiber membrane. The prepared graphene heating film for heater is recorded as Comparative Example 5.
[0110] Comparative Example 6:
[0111] Compared with Example 1, the difference of Comparative Example 6 is that step S1.2 is not performed, and the spinning solution A prepared in step S1.1 is directly spun, specifically: "S1.1: at room temperature 22°C, potato starch is added to a 2.0wt% NaOH aqueous solution and stirred continuously for 3h to form a potato starch solution, the material-liquid ratio of potato starch to NaOH is 3:10g / L, then an equal volume of PTFE emulsion is added to the potato starch solution, stirring is continued for 2h, and standing is performed for 3h to obtain a spinning solution A;
[0112] S1.2: Place the spinning solution A in a spinneret, select a dispensing needle with a needle specification of 25G, set the centrifugal speed to 900rpm, set the collection distance to 95mm, and perform centrifugal spinning in an environment with a humidity of 45% and a temperature of 40°C to obtain a composite PTFE fiber membrane. The prepared graphene heating film for heater is recorded as Comparative Example 6.
[0113] The long-term heating data of Examples 1-3 and Comparative Examples 1-6 were measured with reference to the test methods of GB / T7287-2008 and JG-T286-2010. The test time was 72 hours. Starting from 24 hours, the stable temperature was tested every 12 hours. The test voltage was 4 V, as shown in Table 1.
[0114] Table 1
[0115]
[0116] The stable temperature of Example 1 is between 226.1-235.7°C, the stable temperature of Example 2 is between 222.3-236.6°C, and the stable temperature of Example 3 is between 220.8-239.7°C. It can be seen that the temperature fluctuates little after long-term heating and the thermal stability is good.
[0117] The stable temperature of Comparative Example 1 is between 227.5-271.8°C, and the stable temperature of Comparative Example 2 is between 248.4-298.2°C. The stable temperatures of both are in the normal operating temperature range of 220-250°C for the heater within 24 hours, but the stable temperature increases significantly after long-term use. It can be seen that in Comparative Example 1, there is no DMSO, and the binding property of cellulose acetate and starch decreases. After long-term work, the composite film is easily decomposed, resulting in a decrease in thermal stability. Comparative Example 2 relies solely on the combination of starch and DMSO, and its thermal stability is not as good as that after adding cellulose acetate. This shows that the composite membrane prepared by introducing starch through DMSO and the composite spinning solution B of starch, DMSO and cellulose acetate has better thermal stability.
[0118] Similarly, the stable temperature of Comparative Example 1 is between 227.5-271.8°C, the stable temperature of Comparative Example 3 is between 271.6-299.6°C, and the stable temperature of Comparative Example 4 is between 274.5-303.4°C. It can be seen that potato starch and starch powder improve the stability of the membrane when preparing the graphene heating film, and the cellulose and PTFE are cross-linked through starch mutual compatibility, further improving the thermal stability of the membrane. Therefore, the temperature of Comparative Example 4 without the addition of potato starch and starch powder rises significantly after long-term use.
[0119] The stable temperature of Comparative Example 5 is between 282.4-319.5°C, and the stable temperature of Comparative Example 6 is between 286.7-329.7°C. It can be seen that the effect of using spinning solution A and spinning solution B in combination is much better than using either of them alone. Moreover, a single spinning solution will increase the overall heating temperature of the graphene heating film, which is not conducive to its application in heaters.
[0120] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a graphene heating film for a heater, characterized in that: The steps include: S1: Preparation of composite PTFE fiber membrane The PTFE emulsion is added to the potato starch solution, stirred and allowed to stand to obtain a spinning solution A, starch powder and DMSO are mixed, cellulose acetate is added, heated and stirred to obtain a spinning solution B, the spinning solution A and the spinning solution B are mixed in equal volumes, placed in a spinneret for centrifugal spinning, and a composite PTFE fiber membrane is obtained; S2: Preparation of starch-coated epoxy resin and epoxy resin adhesive Dissolving water-soluble starch in deionized water to obtain a liquid medium, and then adding epoxy resin to the liquid medium to prepare starch-coated epoxy resin; adding graphene powder to deionized water to obtain a graphene dispersion, mixing concentrated sulfuric acid and concentrated nitric acid to prepare a mixed acid, mixing the mixed acid with the graphene dispersion to prepare treated graphene, adding the treated graphene to an emulsifier PEG for ultrasonic dispersion to obtain a treated liquid, and then adding the treated liquid to the epoxy resin for mixing to obtain an epoxy resin adhesive; S3: Preparation of cross-linked composite membrane The starch-coated epoxy resin and the composite PTFE fiber membrane are cross-linked, cleaned and dried to obtain a cross-linked composite membrane; S4: Preparation of graphene heating film for heaters Graphene is mixed with deionized water to form a graphene suspension, and then the cross-linked composite film and the graphene dispersion are hot-pressed to obtain a conductive heating film. Wires are connected to the conductive heating film, and then epoxy resin adhesive is coated and the cross-linked composite film is attached, and hot-pressed to obtain a graphene heating film for heaters.
2. The method for preparing a graphene heating film for a heater according to claim 1, characterized in that: Step S1: preparing a composite PTFE fiber membrane, comprising the following steps: S1.1: At room temperature of 22-26°C, potato starch is added to a 2-2.5wt% NaOH aqueous solution and stirred continuously for 3-4h to form a potato starch solution, wherein the material-liquid ratio of potato starch to NaOH is 3:(10-11)g / L, and then an equal volume of PTFE emulsion is added to the potato starch solution and stirred for 2-3h, and then allowed to stand for 3-4h to obtain a spinning solution A; S1.2: Mix starch powder and DMSO and heat in a water bath to 70-80°C, the starch powder and DMSO solid-liquid ratio is 1:(9-10) g / L, stir magnetically for 20-24 hours to obtain spinning solution, add 10-12% of the total mass of cellulose acetate to the spinning solution, heat and stir again for 30-40 minutes, let stand to degas, and obtain spinning solution B for standby use; S1.3: Mix spinning solution A and spinning solution B in equal volumes, place in a spinneret, centrifuge at a speed of 900-1000 rpm, collect at a distance of 95-100 mm, and perform centrifugal spinning at a humidity of 45-50% and a temperature of 40-60° C. to obtain a composite PTFE fiber membrane.
3. The method for preparing a graphene heating film for a heater according to claim 2, characterized in that: The spinneret needle in step S1.3 has a specification of 25G dispensing needle.
4. The method for preparing a graphene heating film for a heater according to claim 1, characterized in that: Step S2 is to prepare starch-coated epoxy resin and epoxy resin adhesive, comprising the following steps: S2.1: dissolving water-soluble starch in deionized water at a solid-liquid ratio of 1:(7-8) g / L to obtain a liquid medium, then adding 20-25% of the system mass of epoxy resin to the liquid medium, stirring evenly to prepare a rheological phase, and keeping stirring to react the rheological phase at room temperature of 22-26°C for 2-3 hours. After the reaction is completed, washing with anhydrous ethanol three times, and then drying in a vacuum oven to obtain starch-coated epoxy resin; S2.2: Add graphene powder to deionized water at a solid-liquid ratio of 1:(4-5) g / L to obtain a graphene dispersion, mix concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:(6-7) to prepare a mixed acid, wait for the mixed acid to cool to room temperature 22-26°C, add the mixed acid to a reaction vessel and mix it with the graphene dispersion, the volume ratio of the mixed acid to the graphene dispersion is 3:(4-5), put it in a constant temperature water bath at 60-80°C, start the reaction and stir for 2-3h, wash the product repeatedly with distilled water and anhydrous ethanol, filter it until it is neutral, and then place it in a vacuum oven at 55-65°C to dry for 18-20h to obtain treated graphene; S2.3: Add the treated graphene to the emulsifier PEG and ultrasonically disperse for 20-25 minutes. The solid-liquid ratio of the treated graphene and the emulsifier PEG is 1: (3-4) g / L to obtain a treated liquid. Then, add the treated liquid to the epoxy resin and mix them together in a mixer for 30-40 minutes to obtain an epoxy resin adhesive.
5. The method for preparing a graphene heating film for a heater according to claim 1, characterized in that: Step S3 prepares a cross-linked composite membrane, comprising the following steps: S3.1: placing the prepared starch-coated epoxy resin and composite PTFE fiber membrane in a sealed container containing a 25-30% by mass glutaraldehyde aqueous solution, and steam crosslinking at room temperature of 22-26°C for 24-26 hours; S3.2: Then take out the cross-linked fiber membrane, soak it in a 0.1-0.2M glycine aqueous solution for 3-5 hours, and then wash it repeatedly with PBS for 2-3 times to remove the glutaraldehyde solution. Finally, place it in a 40-45℃ oven for ventilation and drying for 4-5 hours to obtain a cross-linked composite membrane.
6. The method for preparing a graphene heating film for a heater according to claim 1, characterized in that: Step S4 prepares a graphene heating film for a heater, comprising the following steps: S4.1: firstly, anhydrous ethanol and graphene are mixed in a solid-liquid ratio of 2:(11-13) g / L, and a graphene dispersion is obtained after ultrasonic treatment, and then deionized water is added to prepare a graphene suspension having a graphene content of 0.5-1 wt%; S4.2: coating the graphene suspension on the surface of the cross-linked composite film, and then placing it on a hot press at a temperature of 55-60° C. and a pressure of 1-1.5 MPa for hot pressing and drying, and after drying, obtaining a conductive heating film; S4.3: Connect two copper foil wires to the graphene-covered side of the conductive heating film, apply a layer of epoxy resin adhesive, and stick a cross-linked composite film on it. Press it on a hot press with a pressure of 1-1.5MPa for 10-30s to obtain a graphene heating film for heaters.
7. A graphene heating film for a heater, which is prepared by the preparation method of the graphene heating film for a heater according to any one of claims 1 to 6.